Sistem Informasi Pelayanan Publik Untuk Pembuatan Buku Pelaut Berbasis WEB (Studi Kasus: Kantor Syahbandar Kelas Utama Tanjung Perak Surabaya) - Tubagus Rizki Fadli; Januar Wibowo; Kurniawan Jatmika (Jurnal Sistem Informasi Universitas Dinamika, 2012)
Seaman book is an official document issued by the State Government containing the physical identity of sailors that are not based on biometric stadar and not as travel documentation and can not substitute for a passport. Sailors are all people who have the qualifications, expertise or skills as a crew. Understanding seaman book is an official document issued by the state government include a full description of legitimate personal and working relationships of seafarers with employers bookkeeper ship, seaman book can serve as a travel document requirements bookkeeper seafarer has CLA Sea (PKL) are still valid. Information Systems Programme Final Project is the Public Service Information System Based WEB Books Sailors Syahbandar Office First Class Tanjung Perak Surabaya is to produce an interactive website on the public service system in the Ministry of Communications, Office of the Directorate General of Sea Transportation Syahbandar Main Class Tanjung Perak Surabaya in accordance with systems and procedures for publishing new boaters, sailors procedure turn old books or lost, and the extension of seaman book. The application of web-based manufacturing seaman book used by this admin will allow an admin to enter data kepelautan are online then this data can be accessed via the internet. Admin can find a book report new sailor, seaman book renewals and sailors lost books. Reports generated in the form of graphs that will facilitate the reporting admin. Keywords : Books sailors, Sailors, Web, Information Systems Services, Admin